Parents' expectations of staff in the early bonding process with their premature babies in the intensive care setting: a qualitative multicenter study with 60 parents - Guillaume Sonia; Michelin Natacha; Amrani Elodie; Benier Brigitte; Durrmeyer Xavier; Lescure Sandra; Bony Charlotte; Danan Claude; Baud Olivier; Jarreau Pierre-Henri; Zana-Taïeb Elodie; Caeymaex Laurence (BMC, 2013)
Abstract Background During the first weeks of hospitalization, premature babies and their parents encounter difficulties in establishing early bonds and interactions. Only a few studies have explored what caregivers can do to meet parents' needs in relation to these interactions and help optimize them. This study sought to explore parents' perception of these first interactions and to identify the actions of caregivers that help or hinder its development. Methods Prospective study, qualitative discourse analysis of 60 face-to-face interviews conducted with 30 mothers and 30 fathers of infants born before 32 weeks of gestation (mean ± SD: 27 ± 2 weeks of gestational age), during their child's stay in one out of three NICUs in France. Interviews explored parental experience, from before birth up to the first month of life. Results Data analysis uncovered two main themes, which were independent of parents' geographical or cultural origin but differed between mothers and fathers. First, fathers described the bond with their child as composed more of words and looks and involving distance, while mothers experienced the bond more physically. Secondly, two aspects of the caregivers' influence were decisive: nurses' caring attitude towards baby and parents, and their communication with parents, which reduced stress and made interactions with the baby possible. This communication appeared to be the locus of a supportive and fulfilling encounter between parents and caregivers that reinforced parents' perception of a developing bond. Conclusions At birth and during the first weeks in the NICU, the creation of a bond between mothers and fathers and their premature baby is rooted in their relationship with the caregivers. Nurses' caring attitude and regular communication adapted to specific needs are perceived by parents as necessary preconditions for parents' interaction and development of a bond with their baby. These results might allow NICU staff to provide better support to parents and facilitate the emergence of a feeling of parenthood.